RANCANGAN USULAN TARIF DAN PERIODE PENYIMPANAN KONTAINER IMPOR DENGAN MODEL OPTIMASI UNTUK MAKSIMASI KEUNTUNGAN DI TERMINAL PETI KEMAS - Nurul Melinia, Anisa
As global import activities continue to increase, the operational activities at terminals also intensify. However, this does not necessarily guarantee an increase in the terminal's profits. The presence of free days at the terminal attracts customers to store imported containers for free for one day, thereby hindering the flow of new container arrivals and terminal operations. Therefore, a proposed design for a new import container storage tariff is put forth, aiming to maximize terminal profit by leveraging data and conditions specific to the Koja Container Terminal (TPK).